2023
DOI: 10.1021/acs.orglett.3c00542
|View full text |Cite
|
Sign up to set email alerts
|

Hydrazine–Halogen Exchange Strategy Toward N═N-Containing Compounds and Process Tracking for Mechanistic Insight

Abstract: An anhydride-promoted traceless hydrazine–I/Br exchange strategy is reported, where hydrazine hydrate and cyclic/linear iodonium, including rarely explored cyclic bromonium, are converted to benzo­[c]­cinnolines/azobenzenes in one pot. The reaction proceeds through diacylation (first and second CN formation), N,N′-diarylation (third and fourth CN formation), and deacylation/oxidation (2 CN cleavages and 1 NN formation). The reaction mechanism is investigated by isolating multiple intermediates and kinetic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 48 publications
0
6
0
Order By: Relevance
“…In recent years, construction of -N=N- bonds using hydrazine hydrate as an inorganic dinitrogen source has received much attention, being a direct and green pathway for the synthesis of aromatic azo compounds. Xie et al reported a copper-catalyzed diarylation reaction of hydrazine with cyclic/linear diaryl iodonium salts, which converted inorganic hydrazine into organic nitrogen-containing compounds to obtain a series of azobenzene derivatives, as shown in Figure 24 [ 97 ]. In this strategy, phthalhydrazide (PHA) was first formed via the hydrazinolysis of phthalic anhydride.…”
Section: Advances In the Synthesis Of Aromatic Azo Compoundsmentioning
confidence: 99%
“…In recent years, construction of -N=N- bonds using hydrazine hydrate as an inorganic dinitrogen source has received much attention, being a direct and green pathway for the synthesis of aromatic azo compounds. Xie et al reported a copper-catalyzed diarylation reaction of hydrazine with cyclic/linear diaryl iodonium salts, which converted inorganic hydrazine into organic nitrogen-containing compounds to obtain a series of azobenzene derivatives, as shown in Figure 24 [ 97 ]. In this strategy, phthalhydrazide (PHA) was first formed via the hydrazinolysis of phthalic anhydride.…”
Section: Advances In the Synthesis Of Aromatic Azo Compoundsmentioning
confidence: 99%
“…In general, arylchloronium and arylbromonium derivatives have higher reactivity toward nucleophilic organic substrates compared to aryliodonium salts, which justifies synthetic interest in these compounds. It should be noted that previously prepared dibenzobromolium and dibenzochlorolium derivatives were limited to tetrafluoroborate, ,, hexafluorophosphate, iodide, chloride, triflate, ,, tosylate, and tetraarylborate salts. It is well known that there is a significant secondary bonding between the iodine atom in aryliodonium salt and the counteranion, which has a strong effect on the reactivity of aryliodonium species .…”
Section: Introductionmentioning
confidence: 99%
“…The analogous dibenzobromolium and dibenzochlorolium derivatives have been less investigated despite been known since 1952 . Very recently, several important synthetic applications of dibenzobromolium salts have been reported, such as halogen-bonding organocatalysts, reagents for cross-coupling reactions with anionic nucleophiles, as aryne precursors in cycloaddition reactions, and reagents for one pot synthesis of benzo­[ c ]-cinnolines and azobenzenes . Synthetic utilization of dibenzochlorolium salts as aryne precursors has recently been reported .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…11 Very recently, Li also reported a meta -selective cross anion–cation coupling of cyclic diarylbrominium tosylates with alcohols and phenols. 12 Considering the importance of halogen-containing biaryl skeletons in pesticides and medicinal chemistry (Scheme 1b), 13 as well as our research interest in diaryliodonium salt chemistry, 14–16 we envision that utilizing cyclic diaryliodonium salts as aryne precursors might make them appealing in transition metal-free regioselective transformations for the construction of valuable 2,3′-dihalobiaryls (Scheme 1d).…”
mentioning
confidence: 99%